Profile of pyoderma in dermatology outpatient departement at Sanglah General Hospital Denpasar, Bali-Indonesia period January 2016 until December 2017 - Ni Luh Putu Ratih Vibriyanti Karna; Dewi Gotama; Sissy (Explorer Front, 2018)
Introduction: Pyodermas are infections in the epidermis, just below the stratum corneum or in hair follicles. It is most common in children, although it can also affect adults. Pyoderma often found in tropic areas. Pyoderma is caused by Staphylococcus, Streptococcus, or both. This study aimed to identify the profile of pyoderma in Dermatology Outpatient Department at Sanglah General Hospital Denpasar Periods January 2016 – December 2017. Method: Study design using descriptive retrospective model, done by taking data from daily visit record in Dermatology Outpatient Department at Sanglah General Hospital Denpasar Periods January 2016 – December 2017. Result: Pyodermas is one of the common skin problems observed in patients attending dermatology OPD. The number of new cases in pyoderma is 202 cases (7,32%), often found in males and 0-5 years age group (35,64%). The diagnosis of furuncle is the most finding type of pyoderma and the most commonly given therapy is a combination therapy of systemic antibiotics with topical. Co-amoxiclav is the most common drug that uses orally and fusidic acid as topical ointment. Conclusion: pyoderma remains as the most common skin infection in dermatology outpatient department at Sanglah General Hospital, Bali-Indonesia. Introduction: Pyodermas are infections in the epidermis, just below the stratum corneum or in hair follicles. It is most common in children, although it can also affect adults. Pyoderma often found in tropic areas. Pyoderma is caused by Staphylococcus, Streptococcus, or both. This study aimed to identify the profile of pyoderma in Dermatology Outpatient Department at Sanglah General Hospital Denpasar Periods January 2016 – December 2017. Method: Study design using descriptive retrospective model, done by taking data from daily visit record in Dermatology Outpatient Department at Sanglah General Hospital Denpasar Periods January 2016 – December 2017. Result: Pyodermas is one of the common skin problems observed in patients attending dermatology OPD. The number of new cases in pyoderma is 202 cases (7,32%), often found in males and 0-5 years age group (35,64%). The diagnosis of furuncle is the most finding type of pyoderma and the most commonly given therapy is a combination therapy of systemic antibiotics with topical. Co-amoxiclav is the most common drug that uses orally and fusidic acid as topical ointment. Conclusion: pyoderma remains as the most common skin infection in dermatology outpatient department at Sanglah General Hospital, Bali-Indonesia.